2022
DOI: 10.1021/acs.accounts.2c00335
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organic Frameworks: Exploring Water-Soluble, Regular Nanopores for Biomedical Applications

Abstract: organic frameworks improve the safety of clinically used porphyrin photodynamic agents and maintain their antitumor efficacy. Biomaterials 2022, 284, 121467. 3 The f irst report of suppressing the posttreatment phototoxicity of residual photodynamic agents, realized through the inclusion of SOFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Since 2013, a variety of well-defined self-assembled porous systems termed supramolecular organic frameworks (SOFs) have been constructed in water. 29,30 SOFs and HOFs are organic molecular frameworks which are discussed in this review (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2013, a variety of well-defined self-assembled porous systems termed supramolecular organic frameworks (SOFs) have been constructed in water. 29,30 SOFs and HOFs are organic molecular frameworks which are discussed in this review (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, in the SOF-3/PES beads, the pores were not as flat and smooth as the pure beads, indicating that SOF-3 powders were loaded and maintained their spongy-like pores. Previous studies showed that SOFs have very low surface areas but efficiently adsorb organic guests driven by hydrophobicity and/or ion-pairing electrostatic interaction . It is thus reasonable to propose that the adsorption of bilirubin by PES bead-supported SOF composites should take place through a similar mechanism.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies showed that SOFs have very low surface areas 40 but efficiently adsorb organic guests driven by hydrophobicity and/ or ion-pairing electrostatic interaction. 53 It is thus reasonable to propose that the adsorption of bilirubin by PES beadsupported SOF composites should take place through a similar mechanism. The above modeling studies showed that all four SOFs possessed a comparable or identical pore aperture or void volume.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[44] The simulated 1 : 2 host-guest structures of Guest 2 �GBox-4 4 + indicated that guest molecules can be stably located in the two host cavities via typical donor-acceptor interactions (Figures 2e, S42-S45). This 1 : 2 host-guest cyclophane motif is reminiscent of the ternary supramolecular system comprising a cucurbit-[8]uril host and two aromatic guests, [45][46] which has been extensively employed to construct various systems including artificial receptors, [47] supramolecular organic frameworks [48][49] and polymers. [50] Taking high solubility of GBox-4 4 + and convenient derivatization of the 3,3'-bipyridinium moiety into consideration, our ternary assembly motif Guest 2 �GBox-4 4 + is a promising subunit for constructing complex multicomponent systems such as mechanically interlocked molecules, molecular machines or supramolecular polymers, which will be reported elsewhere.…”
Section: Resultsmentioning
confidence: 99%